Pengaruh Motivasi dan Kompetensi terhadap Kinerja Pegawai Dinas Kehutanan Kabupaten Muara Enim - A. Rifai, Rusdy (Jurnal Ilmu Manajemen, 2012)
The purpose of this research is to know the influence of motivation and competence 52 employees of Forestry Office District Muara Enim for employee performance. The problem is the motivation and the competence of the employees of Forestry Office District Muara Enim is very low. The analysis which used in this research is multiple linier regression analysis, F test and t test. Based on first hypothesis testing (F test) knew that there are positive influence between motivation and competence for employee performance. It can be seen from F-arithmetic and F-table of ?=0,05 which used determinant coefficient 0,493 or 49,3% and 50,7% was explained by the other factors aside from motivation and competence Based on second hypothesis testing (t test) knew that there are positive influence of motivation variable for employee performance. It can be seen from T-arithmetic and t-table of ?=0,05 which motivation variable for employee performance is 0,372 or 37,2& and 62,8% was influenced by other variable aside from motivation variable Based on third hypothesis test (t test) knew that there are positive influence of competence for employee performance. It can be seen from T-arithmetic and t-table of ?=0,05 which competence variable for employee performance is 0,468 or 46,8% and 53,2% was influenced by other variable aside from competence variable